Morphological restructuring of smooth muscles elements of the wallgreat saphenous vein of a person on the lower leg during the development of varicose transformation - A. B. Sannikov; E. V. Shaydakov (Амбулаторная хирургия)
Introduction. Further study of the structural restructuring of the wall of the great saphenous vein throughout a person’s life with the development of chronic venous diseases is an urgent task of phlebology.The purpose of the study. Research of the morphological restructuring of smooth muscleselements of the human great saphenous vein wall on the calf in norm, ectasia and development of varicose transformation.Materials and methods. The study of morphological restructuring of the great saphenous vein wall on the calf was carried out in 3 comparison groups by light microscopy. In 1th group, the structure of the GSV wall was studied on autopsy material of people who died from various causes at the age of 5 to 80 years. In the 2nd and 3rd groups, fragments of GSV in the calf were taken by biopsy during the execution of the operations for varicose veins. All patients underwent ultrasound mapping before surgery to determine the presence and degree of ectasia, varicose transformation and retrograde blood flow. For histological analysis in the groups, 140 GSV fragments were removed in 1-group, 165 BPV fragments in 2-group, and 250 GSV fragments in 3-group.Results. The general morphological analysis of histological preparations made it possible to visually identify various variants of changes in smooth muscleselements inherent in the inner, middle and outer shells of the GSV wall. The selected variants of reconstruction of the smooth muscleselements were combined into 10 morphological types.Conclusion. Age-related morphological changes in the smooth muscleselements in the GSV wall on the calf, over the course of a person’s life, do not have the same character as changes occurring in its wall during the development of its ectasia and varicose transformation.